Nexus between Insurance Sector Development and Economic Growth in South Asian Countries - Bahadur Budhathoki, Prem; Bhattarai, Ganesh (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: This study examines the impact of insurance sector development on economic growth in South Asian countries. Design/methodology/approach: Using annual data from five South Asian countries over 31 years (1990-2020) and comprising 137 observations, this study draws data from the Global Financial Development Database (2023). The unit root test, cointegration test, and vector error correction model are employed to test stationarity, long-run relationships, and short-run and long-run dynamics, respectively, in South Asian countries. Findings: The findings are significant, revealing that long-term dynamics prevail between the LNGDP and LIPTGDP for five South Asian countries. The coefficient valueof ECTt-1 is -.765, indicating that deviation from the long-run relationship is corrected at 76.5% in the present period. This study further reveals long-term dynamics betweenthe LNGDP and NLIPTGDP for five South Asian countries. The coefficient value of ECTt-1 is -.654, implying that deviation from the long-run relationship is corrected at 65.4% in the present period. Similarly, this study reveals long-term dynamics between the LNGDP and TPC for five South Asian countries. The coefficient value of ECTt-1 is -.765, implying that deviation from the long-run relationship is corrected at a rate of 76.4% in the present period. While no short-run dynamics are observed between the LNGDP and LIPTGDP, between the LNGDP and NLIPTGDP, and between the LNGDP and TPC. Conclusion: The results showed that the LNGDP and TPC had long-term relationships in five South Asian countries. However, no short-run dynamics prevail between the LNGDP and LIPTGDP, between the LNGDP and NLIPTGDP, and between the LNGDP and TPC. Implications: Policymakers can use these findings to promote economic growth by implementing effective regulatory policies, educating the public and SMEs about insurance benefits, providing tax incentives for insurance uptake, and encouraging financial openness for foreign investors to improve consumer choice and quality. JEL Classification: G22, O12, O40